The Leverage cycle - OH, Jaeseung (KDI School, 2015)
The Lehman Brothers’ bankruptcy caused negative impacts on the U.S. and other advanced economies and on the major stock markets across the globe. Though there is a number of a research paper dealing with the impacts of Lehman Brothers’ bankruptcy on the global economic system, only a few research papers have dealt with the causes of Lehman Brothers’ bankruptcy. This paper analyzes the causes of the Lehman Brothers’ collapses on the view point of leverage cycle. Through looking at the financials of Lehman Brothers, this paper extracts the adequate indexes to represent leverage cycle of Lehman Brothers in particular. This paper examines the relationship between policy interest rate and a set of indicators of leverage cycle complied from the annual and quarterly reports of the company. Interest rate has been used as a major indicator to control the economy in the governor’s perspective. Leverage cycle is more direct indicator to the company, as analyzed in Lehman Brothers’ case. Consequently, this paper recommends leverage cycle needs to be considered as additional indicator to control the economy along with interest rate.
Thesis(Master) --KDI School:Master of Public Policy,2015